Bridging the gap between micro and macro forms of engagement: three emerging trends in research on audience participation - Murru, Maria Francesca (2018)
[Excerpt] In this chapter we distil three emergent trends from research on audience practices in a heavily mediated, and increasingly datafied, world (cf. van Dijck 2014), and posit these three trends as potential routes to bridging longstanding gaps between micro and macro forms of audience engagement. First, we identify the dynamics that are at work in the field of micro politics, which pay attention to everyday-life-based engagement with civic meanings and practices, in the context of relentlessly transforming mediated civic cultures. Second, we pay attention to the shaping impact that the micro has on macro politics, thinking, in particular, of organized and institutionalized collective action. We aim to analyse the kinds of dis/connection that seem to be emerging in the interstices between ordinary politics of media practices on the one hand, and macro processes of democratic activism on the other.[...]